The Scientific Authority in Islam from the Perspective of ‘Abd al-Majīd as-Ṣaghīr: The Ideal and the Reality of Knowledge Production - Mutawakkil, Moch. Ali; Putra, J. Nabiel Aha; Wijaya, Roma (An-Nida', 2024)
This study aims to explore the tensions that arise in the production of knowledge by Islamic scholarly authorities between idealism and reality. Numerous studies have examined Islamic religious authorities that produce Islamic knowledge in the form of fatwas, rulings, and opinions. However, existing research has yet to highlight how idealism and reality interact in this production process in the contemporary era. The interplay between idealism and reality in knowledge production has not been thoroughly explored. This study employs a qualitative method with a content analysis approach. The findings reveal that the efforts of Islamic scholarly authorities to ideally produce Islamic knowledge, as conceptualized by ‘Abd al-Majīd as-Ṣaghīr, face various real-world challenges. These include the minority status of Muslims, threats to personal safety from violent actors, a lack of public trust due to scholars holding executive government positions, and the presence of an undereducated (bromocorah) community at the village level. These conditions force Islamic scholarly authorities to postpone the implementation of the ideal model (an-namūdhaj al-mithālī) and adopt various adaptive strategies. This article implies that while Islamic scholarly authorities continue striving to realize their ideal model, the realities they face compel them to adapt and delay its implementation. This narrative sheds light on an aspect that has not been extensively discussed in previous studies. Abstrak: Penelitian ini bertujuan untuk mengungkap bagaimana tarik-ulur yang terjadi pada produksi pengetahuan oleh otoritas ilmiah dalam Islam antara keidealan dan realitasnya. Studi mengenai otoritas agama Islam yang memproduksi pengetahuan keislaman, baik berupa fatwa, keputusan, maupun pendapat, telah banyak dilakukan. Namun, riset yang ada selama ini belum menyoroti bagaimana keidealan dan realitas produksi tersebut di era kekinian. Tarik-ulur antara keidealan dan realitas dalam proses produksi pengetahuan ini belum pernah diungkap secara mendalam. Penelitian ini menggunakan metode kualitatif dengan pendekatan content-analysis. Hasil penelitian menunjukkan bahwa upaya produksi pengetahuan keislaman secara ideal oleh otoritas ilmiah dalam Islam, sebagaimana yang digagas ‘Abd al-Majīd as-Ṣaghīr, menghadapi berbagai kendala dalam realitasnya. Beberapa di antaranya adalah kondisi muslim yang minoritas, ancaman keselamatan jiwa dari aktor kekerasan, kurangnya kepercayaan masyarakat akibat ulama menjabat sebagai pejabat publik di tingkat eksekutif, serta kendala masyarakat kurang terdidik (bromocorah) di tingkat desa. Situasi ini memaksa otoritas ilmiah Islam untuk menunda model ideal (an-namūdhaj al-mithālī) dan melakukan berbagai bentuk adaptasi. Artikel ini memberikan implikasi bahwa meskipun otoritas ilmiah Islam terus berupaya mewujudkan model idealnya, realitas yang dihadapi memaksa mereka untuk menyesuaikan diri dan menunda penerapannya. Narasi ini mengungkap aspek yang selama ini belum banyak dibahas dalam studi terkait.